PWE-019 Incidence of colorectal cancer in nhs greater glasgow and clyde: the impact of deprivation and geographical location. (17th June 2017) - Wright, E; Gordon, O; Vella, M; Moug, S
Abstract : Introduction: The incidence of colorectal cancer (CRC) is higher in Scotland compared to the rest of the UK, with a crude rate of 69.9 vs 63.9 cases per 1 00 000. Previous studies have demonstrated a link between deprivation and CRC incidence (1) . NHS Greater Glasgow and Clyde (GGC) health board covers 6 local council areas and a population of 1, 142, 580. Anecdotally there has been a perception that certain geographical areas have a higher CRC incidence within GGC. The study aimed to determine if there is a link between either deprivation or geographical area and the incidence of CRC in GGC. Method: The local Managed Cancer Network (MCN) database was retrospectively reviewed to identify all new CRC diagnoses in NHS GCC within a 1 year period (2015). The following data was collected: location of the cancer, pathology and patients' postcode. The postcode was used to identify each patients' local council area and Scottish Index of Multiple Deprivation (SIMD) quintile. Briefly, SIMD is a validated measure of deprivation (1=most deprived, 5=least deprived). Patients were excluded if they lived in a council area outwith the six served by NHS GGC. A chi squared test was performed to look for differences between categories. Results: There were 645 new cases of CRC in NHS GGC in 2015. Overall incidence of CRC was 56.5 per 1 00 000. There was a trend towards increased incidence with increasing levels of deprivation; SIMD 1 58.0, SIMD 2 57.3, SIMD 3 57.0, 49.6 and SIMD 5 57.3 cases per 1 00 000 however this was not statistically significant (SIMD 1 and 2 vs SIMD 3–5, p=0.53). There was considerable variation in incidence between different council areas: East Dunbartonshire 57.2, East Renfewshire 69.3, Glasgow City 51.4, Inverclyde 85.1, Renfrewshire 48.2 and West Dunbartonshire 63.5 per 1 00 000. People living in the Inverclyde Council area were significantly more likely to be diagnosed with CRC than those living anywhere else in GGC (p=0.0004). Conclusion: In the area covered by NHS GGC there is significant geographical variation in the incidence of CRC with the Inverclyde Council area having the highest incidence. One possible explanation would be genetic factors. Future work will analyse additional years of data to determine if a similar pattern of incidence is demonstrated that would allow health promotion strategies to be specifically tailored to this high-risk population. Reference: . Cancer Research UK and National Cancer Intelligence Network . Cancer by deprivation in England: Incidence, 1996-2010, Mortality, 1997-2011. London: NCIN; 2014 (accessed at http://www.ncin.org.uk/about_ncin/cancer_by_deprivation_in_england) Disclosure of Interest: None Declared